Genomic analysis of Andamanese provides insights into ancient human migration into Asia and adaptation - Mondal, Mayukh; Casals, Ferran; Xu, Tina; Dall'Olio, Giovanni M; Pybus, Marc; Netea, Mihai G; Comas, David; Laayouni, Hafid; Li, Qibin; Majumder, Partha P; Bertranpetit, Jaume (Nature genetics, 2016)
Jaume Bertranpetit, Partha Majumder and colleagues analyze whole-genome sequences from Andamanese individuals and compare them to sequences from mainland Indian and other geographically diverse populations. They find evidence of ancestry from an unknown extinct hominin in South Asian populations and show that distinct Andamanese characteristics derive from strong natural selection. To shed light on the peopling of South Asia and the origins of the morphological adaptations found there, we analyzed whole-genome sequences from 10 Andamanese individuals and compared them with sequences for 60 individuals from mainland Indian populations with different ethnic histories and with publicly available data from other populations. We show that all Asian and Pacific populations share a single origin and expansion out of Africa, contradicting an earlier proposal of two independent waves of migration 1 , 2 , 3 , 4 . We also show that populations from South and Southeast Asia harbor a small proportion of ancestry from an unknown extinct hominin, and this ancestry is absent from Europeans and East Asians. The footprints of adaptive selection in the genomes of the Andamanese show that the characteristic distinctive phenotypes of this population (including very short stature) do not reflect an ancient African origin but instead result from strong natural selection on genes related to human body size.